Tooth width measurement using the Lythos digital scanner - Bowes Michael; Dear William; Close Emily; Freer Terrence J. (Sciendo, 2017)
Digital models have become more widely accepted for orthodontic diagnostic purposes. Intraoral scanners have the advantage of eliminating the need for conventional impressions. The aim of the present study was to assess the reliability and reproducibility of the Lythos intraoral scanner and to determine if a significant advantage is delivered over stone model and caliper measurements in tooth width and Bolton ratio accuracy.